(untitled) (Journal of Information Technologies in Education (ITE), 2025)
The article examines the features of implementing STEM approaches in the process of preparing future computer science teachers, justifying their importance for meeting the demands of the modern labor market. The rapid development of technology dictates the need not only for solid theoretical knowledge but also for practical skills, flexibility, and innovative thinking. STEM approaches contribute to the development of key competencies such as critical thinking, creativity, and teamwork, which are essential for effective professional activities. The implementation of STEM education is a global trend that requires computer science teachers to adopt a multidisciplinary approach. This includes the use of modern technologies such as programming, robotics, and virtual reality. An analysis of recent research indicates an active interest in STEM in the context of forming professional competencies for computer science teachers, particularly in Ukraine, where the STEM Education Development Concept is being implemented through 2027. This concept aims to develop competencies relevant to the labor market, including algorithmic thinking, creativity, communication skills, and innovation. There is a need for further research into the impact of STEM approaches on the preparation of future computer science teachers. In particular, project-based learning and collaborative learning within the STEM framework ensure the development of both theoretical and practical skills, oriented toward the real needs of professional activity. STEM approaches also promote the integration of interdisciplinary knowledge, making them an integral part of modern education.